EFFECTS OF IDIOMS ON TEACHER RATINGS OF L2 WRITING QUALITY AND LEXICAL DIVERSITY, AND ASSESSMENT CHALLENGES - Abu-Rabiah, Eihab (LLT Journal: A Journal on Language and Language Teaching, 2025)
Idioms are often seen as signs of advanced language proficiency, yet their role in writing assessment is given little consideration. Most research has focused on how idioms are processed cognitively, leaving open questions about how they affect teacher judgments, particularly in second language writing. This study explores how idioms affect teacher ratings of lexical diversity and writing quality, while also highlighting the challenges teachers face in evaluating them. Using a mixed-methods design, twenty Hebrew teachers assessed fifteen essays written by native Arabic speakers, along with revised versions of each essay that included a frequent idiom (30 essays total). The essays spanned CEFR levels A2 to B2 and were randomly ordered. Teachers, whether native speakers of Arabic or Hebrew, rated both lexical diversity and writing quality of each essay on a 10-point scale. Six teachers also participated in semi-structured interviews, which were subjected to thematic analysis. The findings indicate that essays with idioms were rated significantly higher in both writing quality and lexical diversity, regardless of the rater’s first language. The interviews highlighted several recurring challenges in assessing idioms, including contextual appropriateness, idiom transparency, frequency of use, grammatical accuracy, and variation between standard and colloquial forms.